Análises bibliométricas da produção científica dos grupos de pesquisa sobre física do estado sólido na América Latina - Fernandez, Rosali Pacheco (1973)
The statistical data of the published scientific production of the Latin American research groups on solid state physics in the period 1967-1971,by year and by type of literature, presents the actual state of the scientific activity of those groups (see part 1) The distribution analysis of the group's scientific production published in journals show the distribution pattern of this data according to Bradford's and Zipf's laws (see part 2) The analyses of intercommunication among groups reveal what is the probability of every pair of groups communicate within the same population of journals. The methodology followed is based on the mathematical model described by Goffman when searching an indirect method of information retrieval (see part 3) On the basis of the foregoing analyses the growth and development of the scientific production along the period studied came to be known. The distribution pattern of data published in journals shows a non-conformity with Bradford's and Zipf's laws. The results achieved from the intercommunication analyses reveals that a significant communication among groups is only achieved at low points of critical probabilities.